2019
DOI: 10.3835/plantgenome2018.12.0102
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Genome Assembly of a Major Quantitative Disease Resistance Locus in Soybean Toward Fusarium graminearum

Abstract: Core Ideas Quantitative disease resistance to F. graminearum was previously mapped in soybean. A major QDRL to F. graminearum characterized for putative candidate resistant genes. Hybrid genome assembly aided identification of genome rearrangement in the QDRL region. Positions of four expressed candidate genes were within the QDRL to F. graminearum. Fusarium graminearum Schwabe [teleomorph: Gibberella zeae (Schweintiz) Petch] has been identified as a pathogen of soybean [Glycine max (L.) Merr.] causing seed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
(185 reference statements)
0
9
0
Order By: Relevance
“…A subsequent study identified four differentially expressed genes that mapped to this QTL located on chromosome 8. These genes included an actin-related protein 2/3 complex subunit, an unknown protein, a hypothetical protein, and a chalcone synthase 3 [315]. This study demonstrated that removal of the seed coat of highly resistant soybean lines makes them susceptible to F. graminareum, indicating that proteins or secondary compounds in the seed coat may be involved in resistance [315].…”
Section: Fusarium Graminareum Root Rotmentioning
confidence: 78%
“…A subsequent study identified four differentially expressed genes that mapped to this QTL located on chromosome 8. These genes included an actin-related protein 2/3 complex subunit, an unknown protein, a hypothetical protein, and a chalcone synthase 3 [315]. This study demonstrated that removal of the seed coat of highly resistant soybean lines makes them susceptible to F. graminareum, indicating that proteins or secondary compounds in the seed coat may be involved in resistance [315].…”
Section: Fusarium Graminareum Root Rotmentioning
confidence: 78%
“…Million et al . (2019) identified a major quantitative disease resistance locus on chromosome 8 that contributed 38.5% of the phenotypic variance toward F. graminearum from a cross, together with other markers, they mapped this QTL to a 305 kb region harboring 36 genes. Ye et al .…”
Section: Discussionmentioning
confidence: 99%
“…The BARCSoySNP6K assay has been applied in various genetic research, e.g., it has been used to construct linkage maps (Lee et al ., 2015), identify QTL/genes controlling a number of traits such as sudden death syndrome resistance (Wen et al ., 2014; Lightfoot et al ., 2018), aphid resistance (Bhusal et al ., 2017; Zhang et al ., 2017), charcoal rot resistance (Vinholes et al ., 2019), Phytophthora sojae , Pythium irregulare and Fusarium graminearum resistance (Stasko et al ., 2016; Million et al ., 2019), salt tolerance (Do et al ., 2018), waterlogging (Ye et al ., 2018), iron deficiency chlorosis (Merry et al ., 2019), nitrogen fixation (Huo et al ., 2019), growth period (Liu et al ., 2016), seed isoflavone content (Li et al ., 2018), oil and fatty acids (Priolli et al ., 2019), protein content (Nascimento et al ., 2018) and yield (Ye et al ., 2018). These studied not only confirmed previously identified QTL but also resulted in the discovery of new QTL, candidate genes or pathways controlling these traits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, performing a hybrid assembly guarantee to take advantage, from one side, of the depth coverage and basecalling quality given by the Illumina reads and, on the other side, to increase the genome contiguity with the ONT reads ( Chen et al, 2020 ). In fact, this method proved to be very successful in fungal genome assembly, either within the Fusarium world ( Million et al, 2019 ; Degradi et al, 2021 ; Dvorianinova et al, 2021 ; Fan et al, 2021 ) or to extended species ( Faino et al, 2015 ; Saud et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%